Entomotoxic potential of hydroalcoholic extract of Eragrostis plana Nees in experimental model of Nauphoeta cinerea Olivier - Angélica Vieira Aguiar; Lana Dorneles Pedroso; Bruna Trindade Borges; Silvane Vestena (Acta Scientiarum. Biological Sciences, 2023)
The objective of this study was to evaluate the entomotoxic activity of the hydroalcoholic extract of Eragrostis plana Nees in an experimental model of cockroaches (Nauphoeta cinerea Olivier), for a possible bioinsecticide. For this purpose, aerial parts of E. plana were grounded to obtain the hydroalcoholic extract (EACA), after preparing the concentrations of (0.5; 2.5; 5.0; 12.5; 25.0; 50.0 100.0 μg g-1 per animal) a saline solution was used to control the treatment. To determine the receptors and pathways involved in responses to EACA doses of E. plana, a treatment with the drug octopamine and its inhibitor phentolamine were prepared. The effect of EACA on behavioral activities (grooming) and on cardiac activity were tested. All data were expressed as mean ± standard deviation, being analyzed by the two-way ANOVA test, followed by the Tukey test, considered significant when p<0.05. After carrying out the experiment, it was found that EACA induced a significant effect on leg grooming at all concentrations, except for the concentration of 100 μg g-1 per animal, but the same did not modulate antenna grooming. Regarding the receptors and pathways involved, it was observed that octopamine alone and together with the extract, had a significant effect on leg grooming, while phentolamine, together with the extract, influenced antennae grooming. Regarding the effect of the extract on the semi-isolated heart, it was noticed that the same doses that affected grooming, affected heart rate by decreasing it. At no concentration, at the end of the treatment, there was no recovery of the heart rate. The results point to a direct modulation of octopaminergic and cholinergic pathways in the insect nervous system.